A Rare Case of a Combination of Tessier Cleft 0 and 3 in a 4-Year-Old Child—A Case Report - Bibhuti Bhusan Nayak; M. Lopamudra (Indian Journal of Plastic Surgery)
Description and successful management of a patient with Tessier no. 0 and 3 facial cleft is being presented. Appropriate evaluation was done to rule out the presence of median cleft face syndrome. Lip cleft was repaired by straight line technique with staggering at the vermilion border. Nasal cleft was reconstructed by a transposition flap and the flap taken from the upper lip after correction of the midline cleft. Satisfactory outcome was achieved for this singular deformity by conforming to the basic tenets of plastic surgery.